2014
DOI: 10.4274/tjod.83723
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of women about elective abortion

Abstract: Objective:The aim of this study was to investigate the opinions of women who presented to the hospital for elective abortion.Materials and Methods:This descriptive study was designed and conducted at our university hospital between March 2013-April 2013 by the method of face-to-face interviews with 500 women who presented to the hospital as patient or relatives of patients. Poll consisted of 6 questions about demographic characteristics and 14 questions evaluating the opinions and attitudes about abortion.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In a study conducted at a university hospital, it was found that only about one-fifth of the participants considered abortion as a natural right, two-thirds approved in case of danger for health, and more than one in ten people wanted strictly that it would not be allowed under any circumstances. 34 In the first 10-12 weeks of the pregnancy, induced abortion was considered as part of the reproductive rights, preventing abortions by reducing unintended pregnancies was seen as an important gain for women's health. 6 This finding of ours suggests that those who know that abortion was legal to use it as a family planning method and also brought about the problem of access to healthcare for women without knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted at a university hospital, it was found that only about one-fifth of the participants considered abortion as a natural right, two-thirds approved in case of danger for health, and more than one in ten people wanted strictly that it would not be allowed under any circumstances. 34 In the first 10-12 weeks of the pregnancy, induced abortion was considered as part of the reproductive rights, preventing abortions by reducing unintended pregnancies was seen as an important gain for women's health. 6 This finding of ours suggests that those who know that abortion was legal to use it as a family planning method and also brought about the problem of access to healthcare for women without knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined in studies that factors, such as a young mother’s age, number and age of children, serious illnesses, death of spouse or divorce, and low education level increase the frequency of application of voluntary abortions (Chiweshe et al, 2017; Koç et al, 2022). In Turkiye, the reasons for women’s voluntary abortion were reported as health problems (37.5%), unwanted pregnancy (26%), being told that their baby would be disabled (9.4%), unplanned pregnancy (52.9%) and medical necessity (47.1%) were reported as main reasons (Çakmak et al, 2015; Koç et al, 2022). Involuntary curettage is an indicator of the unmet need for family planning services in developing countries, and unplanned and unwanted pregnancies are often terminated by induced abortion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in societies where voluntary abortion is condemned, women may hide that they have had a voluntary abortion due to the stigma, exclusion or judgment they face (Makleff et al, 2019). Studies conducted in Turkiye indicate that approximately half of women want voluntary abortion to be banned and that women experience psychological problems after voluntary abortion (Çakmak et al, 2015; Koç et al, 2022). In one study, two out of three women who had an abortion expected to be stigmatized if others found out; 58% stated that they should keep the abortion a secret from their friends and family and felt guilt and shame after the abortion.…”
Section: Introductionmentioning
confidence: 99%